Incubator Penetasan Telur Ayam Berbasis Arduino - Rahmadi Asri; Ratna Dewi; Amna, Amna; Riska Yurianda (UNIVERSITAS STEKOM, 2023)
Naturally, a mother hen incubates her eggs until they hatch completely. However, the success rate of natural hatching is low, and hatching can be completed with a maximum of 10 eggs. Chicken farming, more specifically the chicken egg hatching system, breeders usually use an incubator for the process of hatching chicken eggs. In the incubator, there is a lamp that has been provided which is used for the process of warming the eggs so that the eggs can hatch properly and of good quality with incandescent lamps. In general, the process of hatching eggs often encounters problems or obstacles. The obstacle that is often experienced when hatching chicken eggs is that the incubator only uses incandescent lights. Therefore, to avoid this problem, a microcontroller was designed to overcome this problem. This tool is a combination of a microcontroller with an Arduino-based temperature and humidity sensor. With this tool, after the eggs hatch, when the lights are off, the sensor can read the output in the form of the incubator temperature, which is detected by the Arduino serial display. Design methods and experimental methods were used in this research. Tool testing is divided into three types, namely temperature testing, humidity testing and egg load testing. The result of this research is an automatic egg incubator machine that uses Arduino. Several electronic components used in the incubator are Arduino,